ANALYSIS OF VISUAL PERCEPTUAL SPACE - Rodríguez-Miñón, P.; Fontes, S.; Merino, J. M.; Garriga, A. J. (Anales de Psicología / Annals of Psychology)
Many authors have studied the mathematical representation of the perceptual space (Baird, 1970; Suppes, 1977; Wagner, 1985). These works are fundamental within the psychophysical field since the metricity of the perceptual space is assumed in the different scaling and curve fitting techniques. Our research tries to explain irregularities found in the psychophysical functions for olfactory (Garriga, 1985b, 1987) and tactile (Coello, 1989) data. One suggests that such irregularities are due to the non-Euclidean nature of the perceptual space. Starting with the "psychological" definition of an Euclidean space given in Garriga (1985a) one studies the linearity and metricity components using line length and distance estimations obtained from the extended triangular method. Results show that the visual perceptual space described from our stimuli is not Euclidean.